Respuesta :
x + 2y = 14
-5x + y = 18 --> y = 5x +18
x + 2(5x+18) = 14
x + 10x +36 = 14
11x + 36 = 14
11x = -22
x = -2
sub x = -2 back in one of first two equations:
x + 2y = 14
-2 + 2y = 14
2y = 16
y = 8
x = -2, y = 8
-5x + y = 18 --> y = 5x +18
x + 2(5x+18) = 14
x + 10x +36 = 14
11x + 36 = 14
11x = -22
x = -2
sub x = -2 back in one of first two equations:
x + 2y = 14
-2 + 2y = 14
2y = 16
y = 8
x = -2, y = 8
[tex]x+2y=14\\
-5x+y=18\\
y=18+5x\\
x+2(18+5x)=14\\
x+36+10x=14\\
11x=14-36\\
11x=-22\\
x=-2\\
-5(-2)+y=18\\
10+y=18\\
y=8[/tex]